Method for rapidly determining contents of potassium, sodium, lead and zinc in fly ash for ironmaking

By mixing iron-smelting dust removal ash with starch to prepare it into powder tablets, and synchronous measurements are performed using XRF technology, the problem of long and complex detection time in the iron-smelting dust removal ash in the prior art is solved, and a fast and accurate detection effect is achieved, reducing the detection cost.

CN119534511APending Publication Date: 2025-02-28SHANDONG IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411862321.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art lacks fast and accurate methods to determine the content of potassium, sodium, lead and zinc in iron-smelting dust removal ash, resulting in a long and complex detection time and difficult to meet the urgent detection needs.

Method used

The iron-smelting dust ash and starch were mixed in a certain proportion and prepared into powder tablets, and synchronous measurement was performed using X-ray fluorescence spectroscopy (XRF). By establishing a standard working curve and correcting interference factors, the content of potassium, sodium, lead and zinc was quickly and accurately measured.

Benefits of technology

It realizes rapid and accurate detection of the content of various harmful elements in iron-smelting dust removal ash, eliminates the influence of carbon in the sample, greatly improves the detection efficiency and successful production rate, and reduces the detection cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193487150000041
    Figure BDA0005193487150000041
  • Figure BDA0005193487150000071
    Figure BDA0005193487150000071
  • Figure BDA0005193487150000072
    Figure BDA0005193487150000072
Patent Text Reader

Abstract

The invention belongs to the technical field of chemical analysis, and particularly discloses a method for rapidly determining the content of potassium, sodium, lead and zinc in fly ash for ironmaking, which comprises the following steps: 1) preparing a sample tablet: uniformly mixing powdery fly ash for ironmaking with starch, pressing the mixture into the sample tablet on a tablet press, and drying and storing the sample tablet for detection; and 2) XRF detection: aiming at each index to be detected, setting test conditions on an X-ray fluorescence spectrometer, constructing a standard working curve, and respectively testing the contents of potassium, sodium, lead and zinc in the sample tablets prepared in the step 1) by utilizing the standard working curve. According to the method, the ironmaking fly ash is mixed with starch according to a certain proportion to be made into powder tablets, the content of potassium, sodium, lead and zinc elements in the ironmaking fly ash is synchronously measured through the X-ray fluorescence spectrum, the influence of carbon in a sample is eliminated, the one-time successful tablet making rate is greatly guaranteed, the technology is pioneered, and the measurement result is rapid and accurate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical analysis, and in particular relates to a method for rapidly determining the contents of potassium, sodium, lead and zinc in dust removed for ironmaking. Background Art

[0002] Ironmaking dust, commonly known as blast furnace gas ash, is a product obtained by wet dust removal during the blast furnace smelting process along with the raw materials, fuel dust and particles produced by the intense reaction in the high temperature zone carried by the blast furnace gas. Ironmaking dust contains a large amount of elements such as iron and carbon, and has the characteristics of fine particles, many light substances, easy to disperse and lose, and difficult to store. Direct discharge not only wastes a large amount of resources such as iron and carbon, but also causes serious environmental pollution. Therefore, the development of efficient separation and recycling technology of ironmaking dust as a secondary resource is of great significance to reducing environmental pollution and improving economic benefits. For example, ironmaking dust can be used as a substitute for iron ore and sintered ore in circular production and recycled into sintered ore. Dust ash is a solid waste generated in the steel production process. Harmful elements such as potassium, sodium, lead and zinc in dust ash will gradually enrich during the recycling process, which will have a negative impact on the stable operation of the blast furnace, the quality of steel products, and the longevity of the blast furnace. Therefore, the external discharge of harmful elements in dust ash and the recycling of iron-containing minerals are important contents of circular economy and environmental protection. During the recycling production process, the content of harmful ingredients must be accurately determined to provide guidance for subsequent trade and production use.

[0003] At present, there is no standard analytical method for the determination of potassium, sodium, lead and zinc in dust ash. We can only refer to the detection method of harmful elements in iron ore. The national standard test methods for iron ore mostly use chemical analysis methods or atomic absorption spectrometry, which have complicated test procedures and long measurement cycles, and cannot meet urgent detection tasks. The content of potassium, sodium, lead and zinc in iron smelting dust ash is relatively high, and the linear range of the atomic absorption spectrophotometry curve of the enterprise standard is relatively narrow. The sample solution above the curve range must be diluted a certain multiple to be accurately measured, and when measuring multiple elements, the calibration curve can only be drawn five times to determine the corresponding elements, so the measurement time is relatively long. At the same time, due to the complex composition of iron smelting dust ash, the reducing substances in the dust ash will also interfere with the determination of the content of harmful elements.

[0004] Therefore, how to accurately detect the content of potassium, sodium, lead and zinc in dust ash used in ironmaking has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the drawbacks of the above-mentioned prior art, the present invention discloses a method for quickly determining the contents of potassium, sodium, lead and zinc in dust removed for ironmaking, which adopts the following technical means:

[0006] A method for rapidly determining the contents of potassium, sodium, lead and zinc in dust removed for ironmaking comprises the following steps:

[0007] 1) Preparation of sample tablets: Mix the powdered ironmaking dust and starch evenly, press them into sample tablets on a tablet press, and dry and store them for testing;

[0008] 2) XRF detection: Prepare a sample of the dust removal ash standard sample according to the sample preparation method of step 1), establish a corresponding measurement method on the X-ray fluorescence spectrometer, select the best measurement conditions for each component, correct the existing interference factors, calculate the regression to obtain the corresponding working curve, measure the X-ray fluorescence intensity of the component to be tested under the measurement conditions set by the X-ray fluorescence instrument, the X-ray fluorescence intensity of the sample is proportional to the content, and then use the standard working curve to test the content of potassium, sodium, lead and zinc elements in the sample pressed tablets prepared in step 1).

[0009] Furthermore, in step 1), the mass ratio of the dust removal ash for ironmaking to starch is 5:1.

[0010] Furthermore, in step 1), when the sample is pressed into a tablet on a tablet press, the pressure is 28 to 33 tons and the static pressing time is 28 to 33 seconds.

[0011] Furthermore, in step 2), the test conditions of each indicator to be tested are as follows:

[0012] Component K2O: Analysis line K α , crystal LiF200, collimator 300, detector rPC, tube pressure 50, tube current 60, 2θ / (°) 136.682, PHD1(LL) 120, PHD2(UL) 285;

[0013] Component Na2O: Analytical line K α , crystal RX25, collimator 150, detector rPC, tube pressure 50, tube current 60, 2θ / (°) 46.688, PHD1(LL) 110, PHD2(UL) 305;

[0014] Component Pb: Analysis line L β1 , crystal LiF200, collimator 300, detector rSC, tube pressure 50, tube current 60, 2θ / (°) 33.92, PHD1(LL) 110, PHD2(UL) 290;

[0015] Component Zn: Analysis line K α , crystal LiF200, collimator 300, detector rSC, tube pressure 50, tube current 60, 2θ / (°) 41.78, PHD1(LL)100, PHD2(UL)300.

[0016] Furthermore, the method further comprises the following steps: before preparing the sample tablets, drying the powdered ironmaking dust ash at a temperature of 105 to 110° C. for 1 to 2 hours, and storing it in a dry state before use.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention mixes iron smelting dust with starch in a certain proportion to make powder tablets, and uses X-ray fluorescence spectroscopy to synchronously determine the content of potassium, sodium, lead and zinc in the iron smelting dust, eliminating the influence of carbon in the sample, greatly ensuring the one-time successful tableting rate, and the technology is innovative, and the measurement results are fast and accurate. Samples with high carbon content can also be successfully tableted at one time and then measured using X-ray fluorescence spectroscopy, which not only greatly saves detection time and personnel energy, allowing more work to be done and improving detection efficiency, but also saves electricity and gas costs and reduces detection costs. It is an important innovation in the method for determining the content of multiple harmful elements in iron smelting dust, which can fill the domestic gap in the pre-treatment of such samples and has very strong application prospects and great social benefits. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is clearly and completely described below in conjunction with specific embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect.

[0020] The starch used in the embodiments of the present invention is a common commercial product, and the dust removal ash standard sample YSBC287109 is purchased from Shandong Metallurgical Science Research Institute. The instruments and models used in the embodiments of the present invention are:

[0021] X-ray fluorescence spectrometer: ZSX Primus IV

[0022] Tablet press: ZHY401 / 601

[0023] Example 1

[0024] 1) Preparation of sample tablets: Add starch to the dust ash standard sample YSBC287109 at a mass ratio of 5:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder sample tablets. After marking the pressed tablets, place them in a dryer for testing.

[0025] 2) XRF detection: Prepare the sample tablets of dust removal standard samples according to the method of preparing sample tablets in step 1) for drawing the standard working curve, establish the corresponding measurement method on the X-ray fluorescence spectrometer, select the best measurement conditions for each component (see Table 1), correct the existing interference factors, calculate the regression to obtain the corresponding working curve, measure the X-ray fluorescence intensity of the component to be tested under the measurement conditions set by the X-ray fluorescence spectrometer, the X-ray fluorescence intensity of the sample is proportional to the content, and then use the working curve to test the contents of potassium, sodium, lead and zinc in the sample tablets respectively. The results are shown in Table 2.

[0026] Table 1 XRF measurement conditions

[0027]

[0028] Example 2

[0029] 1) Preparation of sample tablets: Add starch to the dust ash standard sample YSBC287109 at a mass ratio of 4:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder sample tablets. After marking the pressed tablets, place them in a dryer for testing.

[0030] 2) Using the standard working curve prepared in Example 1, the contents of potassium, sodium, lead and zinc in the sample tablets were detected. The results are shown in Table 2.

[0031] Example 3

[0032] 1) Preparation of sample tablets: Add starch to the dust ash standard sample YSBC287109 at a mass ratio of 3:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder sample tablets. After marking the pressed tablets, place them in a dryer for testing.

[0033] 2) Using the standard working curve prepared in Example 1, the contents of potassium, sodium, lead and zinc in the sample tablets were detected. The results are shown in Table 2.

[0034] Example 4

[0035] 1) Preparation of sample tablets: Add starch to the dust ash standard sample YSBC287109 at a mass ratio of 2:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder sample tablets. After marking the pressed tablets, place them in a dryer for testing.

[0036] 2) Using the standard working curve prepared in Example 1, the contents of potassium, sodium, lead and zinc in the sample tablets were detected. The results are shown in Table 2.

[0037] Example 5

[0038] 1) Preparation of sample tablets: Add starch to 5# thermoelectric ash in a mass ratio of 5:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder-like tablets. Mark the pressed tablets and place them in a dryer for testing.

[0039] 2) Using the standard working curve prepared in Example 1, the contents of potassium, sodium, lead and zinc in the sample tablets were detected. The results are shown in Table 2.

[0040] Example 6

[0041] 1) Preparation of sample tablets: Add starch to 5# thermoelectric ash in a mass ratio of 4:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder-like tablets. Mark the pressed tablets and place them in a dryer for testing.

[0042] 2) Using the standard working curve prepared in Example 1, the contents of potassium, sodium, lead and zinc in the sample tablets were detected. The results are shown in Table 2.

[0043] Example 7

[0044] 1) Preparation of sample tablets: Add starch to 5# thermoelectric ash in a mass ratio of 3:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder-like tablets. Mark the pressed tablets and place them in a dryer for testing.

[0045] 2) Using the standard working curve prepared in Example 1, the contents of potassium, sodium, lead and zinc in the sample tablets were detected. The results are shown in Table 2.

[0046] Example 8

[0047] 1) Preparation of sample tablets: Add starch to 5# thermoelectric ash in a mass ratio of 2:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder-like tablets. Mark the pressed tablets and place them in a dryer for testing.

[0048] 2) Using the standard working curve prepared in Example 1, the contents of potassium, sodium, lead and zinc in the sample tablets were detected. The results are shown in Table 2.

[0049] Example 9

[0050] 1) Preparation of sample tablets: Add starch to blast furnace dust sample 1# at a mass ratio of 5:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder sample tablets. Mark the pressed tablets and place them in a dryer for testing.

[0051] 2) The standard working curve prepared in Example 1 was used to detect the contents of potassium, sodium, lead and zinc in the sample tablets, and ICP-AES (standard test method) was used for detection at the same time. The results are shown in Table 3.

[0052] Example 10

[0053] 1) Preparation of sample tablets: Add starch to blast furnace dust sample 2# at a mass ratio of 5:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder sample tablets. Mark the pressed tablets and place them in a dryer for testing.

[0054] 2) The standard working curve prepared in Example 1 was used to detect the contents of potassium, sodium, lead and zinc in the sample tablets, and ICP-AES was used for detection at the same time. The results are shown in Table 3.

[0055] Embodiment 11

[0056] 1) Preparation of sample tablets: Add starch to blast furnace dust sample 3# at a mass ratio of 5:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder sample tablets. Mark the pressed tablets and place them in a dryer for testing.

[0057] 2) The standard working curve prepared in Example 1 was used to detect the contents of potassium, sodium, lead and zinc in the sample tablets, and ICP-AES was used for detection at the same time. The results are shown in Table 3.

[0058] Example 12

[0059] 1) Preparation of sample tablets: Add starch to blast furnace dust sample 4# at a mass ratio of 5:1 and mix well in an agate mortar, then press statically for 30 seconds under a pressure of 30 tons on a tablet press to make powder sample tablets. Mark the pressed tablets and place them in a dryer for testing.

[0060] 2) The standard working curve prepared in Example 1 was used to detect the contents of potassium, sodium, lead and zinc in the sample tablets, and ICP-AES was used for detection at the same time. The results are shown in Table 3.

[0061] Embodiment 13

[0062] In order to verify the precision of the test results of this method, this example uses three levels of standard samples, high, medium and low, to conduct a laboratory repeatability precision test. The results are shown in Table 4.

[0063] Comparative Example 1

[0064] A number of sample tablets were prepared, and the difference from the compression method of Example 1 was that no starch was added.

[0065] Table 2 Test results of Examples 1 to 8

[0066]

[0067] Among them, the standard values ​​of dust removal ash standard sample YSBC287109 are: K2O: 2.15; Na2O: 0.67; Pb: 0.11; Zn: 2.15.

[0068] Table 3 Test results of Examples 9 to 12

[0069]

[0070]

[0071] Table 4: Repeatability test data in the laboratory of Example 13

[0072]

[0073]

[0074] In Examples 1 to 8, starch was added to the dust ash and then mixed and tableted. After tableting, it was found that all tablets were firm. At the same time, according to the comparison of the test results between Examples 1 to 8 in Table 2, it was found that after adding different proportions of starch to the sample and tableting, as the amount of starch added increased, the sample test results showed a significant downward trend. Comprehensive analysis showed that when the sample: starch ratio was 5:1, the test results were more accurate and had no effect on the test strength. In Comparative Example 1, starch was not added for compression, and the tableting effect and the qualified rate of tableting were observed. The statistical results show that about 5% of the samples had poor tableting effects and needed to be repeated.

[0075] It can be seen from Table 3 that the test results of the test method of the present invention are not much different from those of the standard test method ICP-AES, and the results are relatively accurate.

[0076] Based on the test results of Example 13 in Table 4, it can be seen that the test method of the present invention has better precision.

Claims

1. A method for rapidly determining the contents of potassium, sodium, lead and zinc in dust removed for iron making, characterized in that: The steps include: 1) Preparation of sample tablets: Mix the powdered ironmaking dust and starch evenly, press them into sample tablets on a tablet press, and dry and store them for testing; 2) XRF detection: for each index to be tested, set the test conditions on the X-ray fluorescence spectrometer, construct a standard working curve, and use the standard working curve to test the contents of potassium, sodium, lead and zinc in the sample tablets prepared in step 1).

2. The method according to claim 1, characterized in that In step 1), the mass ratio of the ironmaking dust ash to starch is 5:

1.

3. The method according to claim 1, characterized in that In step 1), when the sample is pressed into a tablet on a tablet press, the pressure is 28 to 33 tons and the static pressing time is 28 to 33 seconds.

4. The method according to claim 1, characterized in that In step 2), the test conditions of each indicator to be tested are as follows: Component K2O: Analysis line K α , crystal LiF200, collimator 300, detector rPC, tube pressure 50, tube current 60, 2θ / (°) 136.682, PHD1(LL) 120, PHD2(UL) 285; Component Na2O: Analytical line K α , crystal RX25, collimator 150, detector rPC, tube pressure 50, tube current 60, 2θ / (°) 46.688, PHD1(LL) 110, PHD2(UL) 305; Component Pb: Analysis line L β1 , crystal LiF200, collimator 300, detector rSC, tube pressure 50, tube current 60, 2θ / (°) 33.92, PHD1(LL) 110, PHD2(UL) 290; Component Zn: Analysis line K α , crystal LiF200, collimator 300, detector rSC, tube pressure 50, tube current 60, 2θ / (°) 41.78, PHD1(LL)100, PHD2(UL)300.

5. The method according to claim 1, characterized in that The method also includes the following steps: before preparing the sample tablets, drying the powdered ironmaking dust ash at a temperature of 105 to 110° C. for 1 to 2 hours, and drying and storing it before use.